Juvenile Recurrent Parotitis: The Role of Sialendoscopy - Efimia Papadopoulou-Alataki; Panagiotis Dogantzis; Angelos Chatziavramidis; Sofia Alataki; Panagiota Karananou; Kyriaki Chiona; Iordanis Konstantinidis (International Journal of Inflammation)
Juvenile recurrent parotitis (JRP) is a recurrent parotid inflammation of nonobstructive, nonsuppurative nature. It manifests in childhood and usually resolves after puberty but may also persist into adulthood. JRP is characterized by recurrent episodes of unilateral or/and bilateral parotid swelling with pain, reduction of salivary secretion, swallowing difficulty, fever, and malaise. The cause of this condition remains obscure. Throughout the last two decades, many therapeutic methods have been used in order to reduce the frequency and severity of JRP. During the acute episodes, conservative approaches (antibiotics, analgesics, sialogogues, massage of the parotid gland, and mouth rinses) are used. Parotidectomy has been suggested in rare selective occasions. Recently, a promising concept of sialendoscopy, which is a minimal invasive endoscopic technique, has been applied. This review outlines the literature on JRP focusing on methods and challenges in diagnosing JRP along with the differential diagnosis of JRP and the function of the parotid during JRP. In addition, we describe the treatment options for JRP, pointing out the importance of sialendoscopy as a diagnostic and treatment procedure that offers improvement in patients’ daily life.